SIMULASI SISTEM KONTROL OTOMATIS BEBAN TIDAK SEIMBANG - Fanny J Doringin; Marson James Budiman; Stephy Walukow (JURNAL INTEGRASI, 2019)
Large electric power consumer or consumer with own distribution station, such as Hotel, Office, Shopping center, Industry, etc. The installation is connected with 3 phase electricity, which includes the phase R, phase S and phase T. In the planning and installation of electrical installations conducted by Electrical Expert always refers to the design of the load connected in the phase R, S and T, which is cultivated in equal (equal), but on the operation (ON / OFF) electrical load can not be regulated load balance on each phase, because the operation (ON / OFF) adjusted to the needs of electrical equipment installed on each phase, resulting in unbalanced loads. Due to unbalanced load in each phase can cause the loss of electric power. The losses of electric power will be greater, if the addition of load or the development of electrical installation is done without regard to the initial design of the installation. In this research will be made a simulation of control system that will automatically minimize the occurrence of unbalance between phases. The control system will work automatically to adjust the load between phases, by transferring a large detectable load on one phase to a small detectable phase until it is detected that the loads on the R, S and T phases are relatively balanced. In addition, the control system can also detect if one or two missing phases (OFF) occurs, where the system will provide information to the alarm in the form of alarms, indicating that there has been a phase loss, in order for the user to perform a complete electrical outage action for avoid major power losses. The method used in making the system is the method of research and development, with stages including literature study, field study to obtain data in connection with system manufacture. The next step is designing hardware and software that is simulated through the Proteus program. The next stage is to test the work of the control system based on system algorithms created through the simulation program. From the test result, when the load unbalance occurs, for example the load detected in the R Phase of 2 Ampere, at S phase 1.5 Ampere and at the T Phase of 1 Ampere, the system will automatically move one of the power lines from Phase R to one of the paths of the T-Phase, so that the overload present in Phase R is overcome by Phase T, besides that when indicated there is one phase missing, then the system will inform through the alarm and display on the LCD monitor that there is a phase lost.